Training Program for Manufacturing Organic Plant Pots from Waste Materials within the Framework of P5 - Deni Ainur Rokhim; Jacky Anggara Nenohai; Nur Indah Agustina; Zelen Surya Minata; M.Roy Asrori; Hayuni Retno Widarti; Ristiwi Peni; Asnan Wahyudi; Bambang Wahyudi (Journal of Community Practice and Social Welfare, 2023)
The Strengthening Student Pancasila Profile Project (P5) is an implementation of the Merdeka curriculum, in which students undertake a project to enhance their competence and character in accordance with the Pancasila student profile. The community engagement team from Malang State University links the implementation of P5 to themes and project objectives that align with the needs and conditions of our partners. Based on the results of a survey conducted at our partner site, one of the issues identified is a low level of understanding of waste management, especially plastic waste, within the environment of Sidoarjo Public High School 3. Consequently, expert guidance is required to assist our partners in conducting activities related to the production of organic pots from waste materials. This has led to the emergence of an innovation for utilizing and processing waste into organic pots, which can be achieved through P5 activities. The methodology employed in this community engagement project consists of three stages: preparation, observation, and implementation. Data collected include documentation, observations, and the results of respondent questionnaires, which are analysed descriptively and qualitatively. The results of this community engagement project demonstrate that students can generate creative ideas to produce a variety of attractive organic pot products from waste materials. Furthermore, the questionnaire survey distributed to training participants regarding the Pancasila student profile achieved a 100% response rate, indicating that the students comprehend the significance of the Strengthening Student Pancasila Profile Project (P5).